2016
DOI: 10.1186/s12864-016-2725-z
|View full text |Cite
|
Sign up to set email alerts
|

A loss of function variant in CASP7 protects against Alzheimer’s disease in homozygous APOE ε4 allele carriers

Abstract: BackgroundAlzheimer’s disease (AD) represents the most common form of dementia in elder populations with approximately 30 million cases worldwide. Genome wide genotyping and sequencing studies have identified many genetic variants associated with late-onset Alzheimer’s disease (LOAD). While most of these variants are associated with increased risk of developing LOAD, only limited number of reports focused on variants that are protective against the disease.MethodsHere we applied a novel approach to uncover pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 42 publications
2
20
0
Order By: Relevance
“…Genes can be classified into protective and risk genes according to whether their odds ratio (OR) value is greater than one (Ayers et al, 2016;Siezen et al, 2006). There are many ways to score genetic risk (Agerbo et al, 2015;Kuchenbaecker et al, 2017).…”
Section: Construction Of Various Gene Scoresmentioning
confidence: 99%
“…Genes can be classified into protective and risk genes according to whether their odds ratio (OR) value is greater than one (Ayers et al, 2016;Siezen et al, 2006). There are many ways to score genetic risk (Agerbo et al, 2015;Kuchenbaecker et al, 2017).…”
Section: Construction Of Various Gene Scoresmentioning
confidence: 99%
“…Although most studies utilize Caucasian populations, further risk variants have been identified through next-generation sequencing in African-American individuals within the gene AKAP9 (Giri et al, 2016; Logue et al, 2014). Conversely, protective variants have also been identified including a small coding deletion (rs10553596) within the CASP7 gene associated with reduced incidence of AD among individuals with the APOE ε4ε4 genotype in 4 independent imputed data sets (Ayers et al, 2016). Further protective rare variants have also been identified by imputation of previous data sets such as the PLCG2 gene (Sims et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In light of this complexity, there is need to identify convergent neural substrates and underlying molecular mechanisms that can serve as entry points to prevent or reverse disease progression. Along the same lines, identification of genetic mutations or variants that confer protection against disease via loss-offunction effects (LoF), akin to those of a therapeutic agent, hold great promise for devising therapeutic schemes (2)(3)(4)(5) to restore or prevent some or all disease symptoms, either in all patients or, more likely, in specific subsets of patients with well-defined genetic lesions of affected pathways. A well-established example is provided by studies of the PCSK9 locus, where therapeutic agents designed to inhibit PCSK9 were prospectively developed in response to the detected protective effects of PCSK9 LoF variants on LDL cholesterol levels and coronary artery disease risk (6,7).…”
mentioning
confidence: 99%